Analysis of the Use of Distance Learning Technology in Universities in the Riau Islands Province with the Technology Acceptance Model (TAM) - Hendi Sama; Tony Wibowo; Tukino (Postgraduate, University of Mataram, 2023)
The problem that is the focus of the research is the use of distance learning technology at universities in the Riau Islands Province using the Technology Acceptance Model approach. This research aims to analyze user perceptions on ease of use, usability, usage behavior, and use of distance learning technology. This research aims to determine user perceptions of distance learning technology in universities in the Riau Islands Province. Apart from that, this research also aims to evaluate the influence of the ease of use perspective, usability perspective, and usage behavior on the use of distance learning technology. The research results show that research respondents, who are academics and staff at universities in the Riau Islands Province, have a high perception of distance learning technology. From the test results, it was found that there was no significant influence between the ease of se perspective and the usability perspective on the use of distance learning technology. However, usage behavior has a significant influence on the use of distance learning technology. Apart from that, these three variables together have an influence of 69.70% on the use of distance learning technology.